Wishful Verses and Their Synonyms in the Qur’anic Context: A Graphic Objective Study - Khalaf Mahmud, Safarjal Shukur (Journal of Tikrit University for Humanities, 2022)
The contemplator and contemplation of its words will find that Allah Almighty mentioned them in different places in order to clarify the meaning, and to clarify its purposes and function in the Qur’anic context. The research aims to investigate the positions of wishes in the Holy Qur’an, and study them as an objective interpretive study in order to understand their meanings and to explore and elucidate the semantic potentials, and to show what they contain from the wonderful graphic representation that the Holy Qur’an came. Hence, my research came to be marked with ( Wishes in the Qur’anic Context - an objective Qur’anic study) a continuation of the efforts of those who preceded me in this field, and my desire to gain more knowledge from the Holy Qur’an; So I started the research by defining wishes, linguistically and idiomatically, then dividing the research into two demands. The first requirement included: the words of wishes in the context of the Noble Qur’an. Then the research added the second requirement with synonyms of wishes in the Holy Qur’an, and each demand was interspersed with some Qur’anic examples to clarify the meaning through the Qur’anic context. The last part of the study is the conclusion